Challenges Faced by Older Workers in Thailand: Age Discrimination and Its Economic Impact - Chayutrakorn, Chalita; Jangkham, Sarunyar; Bhornsuthaworaphat, Thanakorn; Lertkowit, Pipat; Sari Supriyanti , Ratna; Tubpond, Teerapong (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Thailand is facing significant demographic changes, with a growing aging population due to lower fertility rates and longer life expectancy. This paper examines the challenges that older workers in Thailand’s labor market encounter, particularly focusing on age discrimination and its economic consequences. Despite existing legal protections against age-based discrimination, many older workers, especially those aged 65 and above, continue to face barriers in securing stable and well-paying jobs. These barriers include age-related biases regarding their adaptability, technological skills, and productivity. As the working-age population shrinks, older workers are often pushed into informal, low-wage sectors that lack adequate social protection, increasing economic inequality. Moreover, limited access to retraining and skills development opportunities, particularly in rural areas, makes it harder for older workers to adapt to the demands of modern industries. The economic impact of this exclusion is severe, as it contributes to reduced labor force participation, social marginalization, and greater financial insecurity. To address these challenges, the paper advocates comprehensive policy reforms that focus on reducing age discrimination, expanding social protection, and investing in skills training and career support for older workers. By creating a more inclusive workforce, Thailand can ensure that older workers remain valuable contributors to the economy, even in the face of demographic and technological shifts.